2023
DOI: 10.3390/lubricants12010007
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Dynamic Characteristics of Gears Considering Surface Topography in a Mixed Lubrication State

Gong Cheng,
Jianzuo Ma,
Junyang Li
et al.

Abstract: Based on mixed lubrication analysis, considering the influence of rough interface contact stiffness, contact damping, and interface friction on the gear transmission system, the relationship between interface contact and the overall performance of the gear transmission system has been established. First, the surface topography is characterized using statistical parameters of rough surfaces, and the contact stiffness and damping for tooth surfaces with different roughnesses are calculated. Subsequently, a six d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…They investigated the dynamic characteristics of the system that suffer from both the internal gear meshing forces and the random wind load. Cheng et al [19] developed a tribo-dynamic model of a PGS with a rough interface on the contact stiffness, damping, and friction forces. They found that surface roughness has a great influence on the system vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the dynamic characteristics of the system that suffer from both the internal gear meshing forces and the random wind load. Cheng et al [19] developed a tribo-dynamic model of a PGS with a rough interface on the contact stiffness, damping, and friction forces. They found that surface roughness has a great influence on the system vibrations.…”
Section: Introductionmentioning
confidence: 99%